Development and standardization of speech test material in bengali - Debashis Ghosh (Journal of All India Institute of Speech and Hearing, 1970)
To evaluate the extent of an individual's handicap may be assessed by assessing his ability to handle speech input. The conventional classical basic audiologic battery for each ear includes four measures of (1) Pure tone air conduction thresholds, (2) Pure tone bone-conduction thresholds, (3) Spondes thresholds (4) An estimation of his discrimination ability.